Guatemala : Request for Stand-By Arrangement-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guatemala. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses a request from the Guatemalan authorities for an 18-month Stand-By Arrangement (SBA) with total access of SDR 630.6 million (about USD 951 million). Guatemala has a strong track record of macroeconomic stability. The economy is open and hence vulnerable to external shocks. The authorities have taken a number of upfront measures to mitigate the impact of the external shock and preserve macroeconomic stability. The program will support the authorities' policies and provide insurance against significant downside risks.